2018
DOI: 10.1038/s41598-018-23894-2
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin 1 sustains the electrophysiological responsiveness of retinal ganglion cells

Abstract: Pannexin 1 (Panx1) forms ATP-permeable membrane channels that play a key role in purinergic signaling in the nervous system in both normal and pathological conditions. In the retina, particularly high levels of Panx1 are found in retinal ganglion cells (RGCs), but the normal physiological function in these cells remains unclear. In this study, we used patch clamp recordings in the intact inner retina to show that evoked currents characteristic of Panx1 channel activity were detected only in RGCs, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 76 publications
(107 reference statements)
0
16
0
Order By: Relevance
“…Altogether, we propose that the altered behavior of panx1a −/− larvae in a dark environment and during light/dark transitions is caused by Panx1a modulating visual inputs through D2-like dopaminergic receptors signaling. In line with this proposal is that a recent study reported Panx1 channel activity currents only in the OFF-type retinal ganglion cells (RGCs) 28 , the neurons responsible for detecting light decrement. Beyond the visual system, a recent behavioral study in Panx1 knock out mice showed that loss of Panx1 induces difficulties in motor control and changes of the sleep-wakefulness cycle.…”
Section: Typ Of Stimulusmentioning
confidence: 74%
See 1 more Smart Citation
“…Altogether, we propose that the altered behavior of panx1a −/− larvae in a dark environment and during light/dark transitions is caused by Panx1a modulating visual inputs through D2-like dopaminergic receptors signaling. In line with this proposal is that a recent study reported Panx1 channel activity currents only in the OFF-type retinal ganglion cells (RGCs) 28 , the neurons responsible for detecting light decrement. Beyond the visual system, a recent behavioral study in Panx1 knock out mice showed that loss of Panx1 induces difficulties in motor control and changes of the sleep-wakefulness cycle.…”
Section: Typ Of Stimulusmentioning
confidence: 74%
“…This mutation caused the generation of a truncated protein. The mutation was distinct from the previously reported panx1a −/− model in which the start codon was targeted 23 , but better compared to the mouse knockout model with deletions of exons3 and 4, which was used previously to investigate sensory processes and learning and memory 9,28 . Similar to other rodents 29,30 and the other zebrafish model 23 , the panx1a −/− zebrafish are viable and fertile, with no apparent anatomical abnormalities or morphologic changes to the eyes.…”
Section: Discussionmentioning
confidence: 91%
“…60 Furthermore, recent findings indicated heterogenous expression of pannexin-1 channels on RGCs, and greater pannexin-1 function was apparent in OFF RGCs. 61 While this could lead to greater calcium influx in OFF RGCs, causing their increased vulnerability following injury, there is evidence that pannexin-1 does not act alone. Studies of cultured cells found both pannexin-1 and the P2X7 receptor were necessary for inducing a large inward current 62,63 which could be capable of potentiating RGC death through excitotoxicity.…”
Section: The Pannexin-1 and P2x7 Receptor Complexmentioning
confidence: 99%
“…Indeed, Chavda et al 62 have found a greater effect of P2X7-R agonists and antagonists on the ON pathways of mice. Calcium-permeable glutamate receptors or associated proteins such as pannexin-1 and transient receptor potential vanilloid (TRPV) channels, have also been shown to be more highly expressed in distinct RGC types 63 65 . Activation of mechanosensitive channels, such as pannexin-1 and TRPV channels, with pressure or cellular swelling lead to calcium influx into the cell and may initiate RGC-type specific apoptosis and death 66 68 .…”
Section: Discussionmentioning
confidence: 99%